Crisis Management, Risk Analysis and Assessment Methods on the Municipal Level - Kąkol, Urszula; Marczewski, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
This article examines crisis management on the municipal level. The rapid reaction of territorial administration units to crisis and the correct assessment of the possibility of it occurring is more and more important. The goal of the article is to identify the risk analysis and assessment methods which are or could be used for crisis management purposes on the municipal level. The risk assessment needs of territorial administration units are defined and the survey results of practical utility of risk analysis and assessment methods is presented. The best risk analysis and assessment practices in the world are also discussed.